PROJECTIONS OF IRAN’S THREAT - KOREIVAITĖ, IEVA (Politologija, 2013)
The article aims to assess Iran’s threat to the international community (especially to the U.S. interests in the Middle East region and Israel’s security) and thereby opposes several stereotypes intervening in Iran’s foreign policy analysis. Evidently, they became a source of erroneous presumptions and induced a securitized policy towards Iran, which can be unnecessary and dangerous for the international community itself.The vastly recognized discourse that Iran is producing mass destruction weapons or even is eager to use them to confront the U.S. and Israel can be indicated as an example of such presumptions. The researcher E. Said has stated that the Middle East region has been mystified and irrationalized. This tendency served as a political strategy to approve imperial ambitions and actions. Unfortunately, the same strategy became an obstacle to clearly understand the current political processes in the Middle East.It is obvious that Iran’s foreign policy is directed against the U.S. and Israel, but the assumption that Iran’s ideological system contradicts the nation state security interests (which inevitably would be affected in case of the nuclear war) has no analytical background. Moreover, the U.S. National Intelligence Estimate and the IAEA reports conclude that no evidences were found to prove the military dimension of Iran’s nuclear program. So, the article proceeds with the analysis of the Iran’s regional power projections to answer the question what the nature of a real Iran’s threat can be.